Modelling of a Two-Stage Bidirectional AC-DC Converter using Wavelet Modulation - H.K. Chiu; Agileswari K. Ramasamy; Nadia M.L. Tan; Matthew Y.W. Teow (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper, a Wavelet modulated isolated two-stage three-phase bidirectional AC-DC converter is proposed for electric vehicle (EV) charging systems. Half-bridge resonant CLLC converter is proposed due to its high efficiency, wide gain range, galvanic isolation and bidirectional power flow. Wavelet modulation technique is used for three-phase six leg AC-DC converter due to its benefits of high DC component and lower harmonic contents. The proposed two-stage converter is developed and simulated in MATLAB Simulink environment. The contribution of this paper is on the implementation and performance analysis of Wavelet modulation in bidirectional AC-DC converters. The results show that Wavelet modulation is suitable to be implemented for the proposed bidirectional converter. The performance of the proposed converter delivers very low output voltage ripple and total harmonic distortion output current of less than 10% which is within the expected results.